Five loop minimal MOM scheme field and quark mass anomalous dimensions in QCD. (16th February 2023) - Gracey, J A; Mason, R H
Abstract: We determine the anomalous dimensions of the gluon, Faddeev–Popov ghost and quark in the minimal momentum subtraction scheme to five loops for a general colour group when quantum chromodynamics is fixed in a linear covariant gauge. The quark mass anomalous dimension is also constructed in the same scheme.